Telephone Surveys Underestimate Cigarette Smoking among African-Americans - Landrine, Hope; Corral, Irma; Simms, Denise A.; Roesch, Scott; Pichon, Latrice; Ake, Diane; Villodas, Feion (Frontiers in Public Health, 2013)
Background. This study tested the hypothesis that data from random digit-dial telephone surveys underestimate the prevalence of cigarette smoking among African-American adults. Method. A novel, community-sampling method was used to obtain a statewide, random sample of N= 2118 California (CA) African-American/Black adults, surveyed door-to-door. This Black community sample was compared to the Blacks in the CA Health Interview Survey (N = 2315), a statewide, random digit-dial telephone-survey conducted simultaneously. Results. Smoking prevalence was significantly higher among community (33%) than among telephone-survey (19%) Blacks, even after controlling for sample-differences in demographics. Conclusions. Telephone surveys underestimate smoking among African-Americans and probably underestimate other health risk behaviors as well. Alternative methods are needed to obtain accurate data on African-American health behaviors and on the magnitude of racial disparities in them.